Guiding People to Interpret Their Experienced Difficulty as Importance Highlights Their Academic Possibilities and Improves Their Academic Performance - Oyserman, Daphna; Elmore, Kristen; Novin, Sheida; Fisher, Oliver; Smith, George C. (Frontiers in Psychology, 2018)
Does experiencing difficulty bolster or undermine future self-images, strategies to get there and actual performance? We build on four insights from prior research to predict that accessible interpretation-of-experienced-difficulty mindset shapes identity and performance. First, people have two different interpretation-of-experienced-difficulty mindsets available in memory; their difficulty-as-impossibility mindset focuses attention on difficulty as implying low odds and their difficulty-as-importance mindset focuses attention on difficulty as implying high value. Second, people are sensitive to contextual cues as to which mindset to apply to understand their experienced difficulty. Third, people apply the mindset that comes to mind unless they have reason to question why it is “on-the-mind.” Fourth, social class can be thought of as a chronic context influencing how much people endorse each interpretation-of-experienced-difficulty mindset. We used subtle primes to guide participants’ attention toward either a difficulty-as-importance or a difficulty-as-impossibility mindset (N=591). Participants guided toward a difficulty-as-importance mindset performed better on difficult academic tasks (Studies 1, 2) than participants guided toward a difficulty-as-impossibility mindset; whether they had more school-focused possible identities and linked strategies depended on sample (Studies 3, 4). For college students, the effect of guided interpretation-of-experienced-difficulty mindset was not moderated by how much participants agreed with that mindset (Studies 1, 3, 4). College students mostly disagreed with a difficulty-as-impossibility mindset, but making that mindset accessible undermined their performance and sometimes their possible identities anyway. In contrast, middle school students (a younger and lower social class sample) were more likely to agree with a difficulty-as-impossibility mindset. In this sample (Study 2), we found an effect of mindset endorsement: agreeing that difficulty implies importance and disagreeing that difficulty implies impossibility improved performance. This study had a control group. Control group participants not guided to use a particular interpretation-of-experienced-difficulty mindset performed no differently than participants guided toward a difficulty-as-impossibility mindset. Results suggest that people may chronically act as if they are using a difficulty-as-impossibility mindset and may benefit from being guided to consider that experienced difficulty might imply task importance. Effect of accessible mindset on salience of academic possible selves was not stable, accessible mindset mattered in one university sample but not the other.